Evaluation of Ecclesial Innovations as Empowerment - Eiffler, Felix (Ecclesial Futures, 2025)
The article introduces the reader to the scientific evaluation of an ecclesial innovation programme initiated in 2015 by the Evangelical Church in Central Germany called Erprobungsräume (Spaces of trial). By doing this, the text sketches the German socio-religious context and discusses the term “ecclesial innovation”. The main part of the article offers and debates the key findings of the evaluation undertaken from 2016 to 2023. The results show how an institution like a German regional church can undergo a broad transformation and what can be learned by this example for innovative church development in general as well as for the scientific evaluation of such a process. Finally, the article connects the evaluation of ecclesial innovation with the discourse on empowerment and outlines the potentials of more participative forms of empirical research as a kind of empowerment.